2016
DOI: 10.1111/tri.12728
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum resistin level and outcomes in kidney transplant recipients

Abstract: SummaryResistin is an adipocytokine that is associated with inflammation, coronary artery disease, and other types of cardiovascular disease among patients with normal kidney function. However, little is known about the association of resistin with outcomes in kidney transplant recipients. We collected socio-demographic and clinical parameters, medical and transplant history, and laboratory data from 988 prevalent kidney transplant recipients enrolled in the Malnutrition-Inflammation in Transplant-Hungary Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In contrast, Chung et al [ 212 ] found that lower serum resistin concentrations were associated with lower survival rates in patients on hemodialysis. Our results also suggest that higher resistin levels have a dose-dependent relationship with risk of graft loss and mortality even after multivariable adjustment in KTRs [ 213 ]. We found that for every 10 ng/mL elevation of serum resistin level there is a 30% increased mortality risk and 73% increased risk of graft loss [ 213 ].…”
Section: Adipocytokines and Outcomes In Ktrsmentioning
confidence: 64%
“…In contrast, Chung et al [ 212 ] found that lower serum resistin concentrations were associated with lower survival rates in patients on hemodialysis. Our results also suggest that higher resistin levels have a dose-dependent relationship with risk of graft loss and mortality even after multivariable adjustment in KTRs [ 213 ]. We found that for every 10 ng/mL elevation of serum resistin level there is a 30% increased mortality risk and 73% increased risk of graft loss [ 213 ].…”
Section: Adipocytokines and Outcomes In Ktrsmentioning
confidence: 64%
“…Hydration has been considered an effective treatment for CA-AKI, but the actual effect of this strategy is still controversial. Perioperative hydration can expand plasma volume by inhibiting the renin-angiotensin-aldosterone system, reducing the concentration of contrast media in the tubule lumen and vasa recta, and counteraction of medullary vasoconstriction activation [40].. It is still the cornerstone of CA-AKI prevention.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review concluded that diabetes is not independently associated with the risk of developing CA-AKI and only increases susceptibility in patients with underlying kidney disease [34]. Regarding contrast volume, current studies suggested that the development of AKI after contrast exposure is signi cantly determined by the presence of comorbidities and hemodynamic instability rather than contrast volume [35,36]. Besides, Mehran et al conducted a recent review and adapted the concept of contrast-associated AKI instead of contrast-induced AKI [1].…”
Section: Discussionmentioning
confidence: 99%